Design and Empirical Validation of a Mid-Range Wireless Power Transfer System Using Magnetic Resonance Coupling - Timsina, Anveshan; Dhital, Sandesh; Nagarkoti, Saroj; Dahal, Utsab; Karkee, Kobid (KEC Journal of Science and Engineering, 2026)
Conventional inductive power transfer is fundamentally limited by the rapid decay of magnetic flux density, restricting efficient energy transmission to near-contact distances. This research addresses this spatial limitation through the design, simulation, and empirical validation of a mid-range wireless power transfer system based on magnetic resonance coupling. The system employs a Class-B push-pull power amplifier driving high-quality factor helical coils with a diameter of 30 centimeters and 6 turns, tuned to a nominal resonant frequency of 1 megahertz. Through integrated finite element method magnetostatic simulations and circuit analysis, the system was optimized to maximize flux linkage while minimizing skin effect losses. Experimental validation demonstrated that the magnetic resonance coupling topology significantly extends transmission range compared to non-resonant inductive coupling. At a separation of 20 centimeters, the resonant system delivered 5.4 volts to the load, whereas the inductive baseline achieved only 0.33 volts. The system achieved a peak end-to-end efficiency of 19.01 percent and maintained functional power transfer up to 40 centimeters. These findings confirm that resonant impedance matching provides a scalable pathway for mid-range charging applications when frequency tracking mechanisms compensate for dynamic coupling variations.